Joan Roura-Parella and his Presence in the United States - Vilanou-Torrano, Conrad (Journal of Catalan Intellectual History, 2011)
The philosopher Joan Roura-Parella, born in Tortellà (Catalonia) in 1897, was an active member of the University of Barcelona Teaching Seminar, from which he obtained his doctorate in 1937 with a thesis supervised by Joaquim Xirau. In 1939, he was a member of the group that accompanied the poet Antonio Machado into exile. After living for a period in Mexico (1939-1945), in 1946 he went to the United States to lecture at Wesleyan University. Under the influence of Krausist philosophy and Quaker spirituality, he explored the humanistic significance of culture, as a result of which his teaching –inspired by the cosmovisionary thinking of Eduard Spranger, with whom he had contacts in Berlin between 1930 and 1932 –took on an aesthetic dimension. With this background, his philosophy of education points towards a vitalist aesthetic formalism, so that education becomes a process –akin to the neo-humanist Bildung tradition– in which an individual develops or gives form to himself throughout his whole life. He died in 1983 in Middletown (Connecticut). key words Joan Roura-Parella, exile, United States, education, Bildung, aesthetics, Catalan pedagogy.